2012
DOI: 10.3810/psm.2012.11.1986
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Review of the Effectiveness of Kinesio Taping for Musculoskeletal Injury

Abstract: Six studies met our criteria and were included in this systematic review. Two of these studies examined musculoskeletal injuries in the lower extremity and reported that the use of KT did not affect outcome measures. Two studies examined musculoskeletal injuries involving the spine. Treatment with KT significantly improved pain levels and range of motion in patients with acute whiplash-associated disorders of the cervical spine both immediately and 24 hours after injury; however, the long-term results did not … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
148
1
10

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 216 publications
(173 citation statements)
references
References 10 publications
5
148
1
10
Order By: Relevance
“…Compared to previous studies, the findings of this review are in agreement with the previous systematic reviews that also found no effects of KT in stroke subjects 16 and other populations [11][12][13] . Apparently, the growing use of KT is due mainly to massive marketing campaigns conducted by the media, ignoring the need for high-quality research, that is, scientific evidence with clinically relevant results 11 .…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Compared to previous studies, the findings of this review are in agreement with the previous systematic reviews that also found no effects of KT in stroke subjects 16 and other populations [11][12][13] . Apparently, the growing use of KT is due mainly to massive marketing campaigns conducted by the media, ignoring the need for high-quality research, that is, scientific evidence with clinically relevant results 11 .…”
Section: Discussionsupporting
confidence: 81%
“…Due to the use of promising KT effects, studies have been developed to investigate the effectiveness of this technique in gait of different populations. In healthy individuals or with musculoskeletal injuries, for example, although isolated studies have demonstrated positive KT results 9,10 , recent systematic reviews do not support the use of this technique on rehabilitation of gait of these populations [11][12][13] . For stroke subjects, studies have also investigated the effects of KT on the gait and also reported promising results 14,15 .…”
Section: Introductionmentioning
confidence: 99%
“…In people with acute musculoskeletal conditions, the effects of KT can significantly improve pain levels and range of motion. In individuals with chronic lumbar pain treated with KT and exercise, KT alone, or exercise alone, experienced a significant improvement in short-term pain, however, the long-term results are uncertain 12 .…”
Section: Methodsmentioning
confidence: 99%
“…(10) Embora o KT tenha sido cada vez mais utilizado no sistema musculoesquelético, nos protocolos e prevenção de esportes de reabilitação lesões, e doenças ocupacionais não ha nenhuma evidência clara sobre potencial mecanismos subjacentes aos seus efeitos benéficos e ha falta de qualidade dos trabalhos. (6,8,11,12) E com a crescente utilização e disseminação da técnica se faz necessário estudos, como este, para esclarecer a cerca das indicações, efeitos perspectivas de seu uso. Porém, 6 artigos estavam presentes em mais de uma base de dados.…”
Section: Métodosunclassified